2016
DOI: 10.1038/gim.2015.133
|View full text |Cite
|
Sign up to set email alerts
|

Participant use and communication of findings from exome sequencing: a mixed-methods study

Abstract: PurposeThis study investigated how genome sequencing results affect health behaviors, affect, and communication.MethodsWe report on 29 participants who received a sequence result in the ClinSeq® study, a cohort of well-educated, post-reproductive volunteers. A mixed methods design was used to explore respondents’ use, communication, and perceived utility of results.ResultsMost participants (72%) shared their result with at least one health care provider, and 31% reported changes to their health care. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 31 publications
(39 reference statements)
7
78
0
Order By: Relevance
“…30 In previous studies, African Americans have shown theoretical interest in genetic testing to learn about risks for kidney disease. 31 We extend these findings to patients who were actually tested and received results. 22,25 …”
Section: Discussionmentioning
confidence: 71%
“…30 In previous studies, African Americans have shown theoretical interest in genetic testing to learn about risks for kidney disease. 31 We extend these findings to patients who were actually tested and received results. 22,25 …”
Section: Discussionmentioning
confidence: 71%
“…As has been previously observed, merely returning results to participants without providing the resources and support necessary to understand and utilize this information can be a potential harm to the participants [21]. Previous studies have shown that negative affective impact of receiving even high impact genetic test results are rare in participants who choose to participate in genetics research projects if counseling about the health implications of results is provided through the research project [22]. Returning results should be considered when developing a research project, as providing adequate funding for staff time and other resources for this activity can be costly [23].…”
Section: Discussionmentioning
confidence: 99%
“…The genomic counseling intervention, in addition to providing more insight into the interrelationship between genetics and health behaviors as contributors of risk, may also have countered existing causal genetic deterministic beliefs and emotions predicated by personal disease experience. This may allow, in turn, greater understanding of the multifactorial nature of complex disease and an opportunity for additional interventions to improve patient-centered health outcomes (Austin, 2015; Lewis et al, 2015; McBride et al, 2015; Ormond, 2013). As all study participants received pre-test education during the informed consent session, and had access to online educational resources, genomic counseling may also have served to reinforce the test report message, and increase confidence in use of multi-page, detailed results.…”
Section: Discussionmentioning
confidence: 99%
“…Given the steady increase in the availability of genomic based results, including those available through online formats, there remains appreciable need for additional research on the effectiveness and extension of genetic/genomic counseling service delivery beyond traditional referral reasons (i.e. Mendelian disease risk) and service delivery approaches (Haga et al, 2014; Lewis et al, 2015; Ormond, 2013; Shiloh et al, 2015; Trepanier & Allain, 2014). These include phone (telemedicine) as well as use of e-learning approaches (both static and interactive) either alone or to supplement counseling (Birch, 2015; Haga et al, 2014).…”
Section: Discussionmentioning
confidence: 99%